Outcomes of Pregnancy in Mothers With Cirrhosis: A National Population‐Based Cohort Study of 1.3 Million Pregnancies - Hannes Hagström; Jonas Höijer; Hanns‐Ulrich Marschall; Catherine Williamson; Michael A. Heneghan; Rachel H. Westbrook; Jonas F. Ludvigsson; Olof Stephansson (Hepatology Communications, 2018)
There are limited data on pregnancy outcomes in women with cirrhosis. To address this gap, we examined the records of singleton births from Sweden’s National Patient Register (NPR), Cause of Death Register (CDR), and Medical Birth Register (MBR) between 1997 and 2011 to assess exposure and pregnancy‐related and liver‐related outcomes of pregnant women with cirrhosis. Exposure status was defined as having an International Classification of Diseases (ICD) code for cirrhosis obtained prior to or during pregnancy. Poisson regression with cluster‐robust standard errors was used to estimate relative risks (RRs) adjusted for maternal age, smoking, and body mass index (BMI). We identified 103 pregnancies in women with cirrhosis and compared these to 1,361,566 pregnancies in women without cirrhosis. Pregnancies in women with cirrhosis were at increased risk of caesarean delivery (36% versus 16%, respectively; adjusted RR [aRR], 2.00; 95% confidence interval [CI], 1.47‐2.73), low birth weight (15% versus 3%; aRR, 3.87; 95% CI, 2.11‐7.06), and preterm delivery (19% versus 5%; aRR, 3.51; 95% CI, 2.16‐5.72). Rates of maternal mortality during pregnancy (no cases), gestational diabetes, preeclampsia, small for gestational age, congenital malformations, and stillbirth were not increased when compared to the pregnant women without cirrhosis. There were 12 hospitalizations during pregnancy due to liver‐related events, including one case with bleeding esophageal varices. Conclusion: Women with cirrhosis are at increased risk for adverse pregnancy outcomes. However, severe maternal and fetal adverse events were rare in our study, and most pregnancies in women with cirrhosis ended without complications.